Partially reversible acute renal cortical necrosis secondary to hyperhomocysteinemia - a case report and literature review - Tan, Wendy; Abd Ghani, Fauzah; Lim, Christopher Thiam Seong (Medknow Publications (India), 2019)
Acute renal cortical necrosis (ACN) is a potentially fatal renal condition. Our objective is to report a case of ACN in a young man who had developed premature atherosclerotic vascular disease and required intermittent hemodialysis support. His renal biopsy showed diffuse cortical necrosis. Subsequently, 2 weeks after the renal insult, he developed a cardioembolic stroke and was anticoagulated with low-molecular-weight heparin. Thrombophilia screen revealed elevated serum homocystein and he was treated with folate supplement and vitamin B12 injection. With these treatments, he had partial renal recovery and became dialysis independent. In conclusion, this is a rare case of ACN, which may have occurred as a complication of hyperhomocysteinemia.